Birth seasonality, fetal loss and air temperature in the Serbia-north region - Vasić Petar; Mirić Natalija (Glasnik Srpskog Geografskog Društva, 2025)
The seasonality of births in Serbia shows a pattern in which the largest number of children are born during late summer and early autumn, placing the largest part of conceptions at the transition from one calendar year to another, which is not the case in the Serbia-North region. Taking into account the seasonality of births, we will try to estimate the distribution of conceptions on a weekly basis during the period 2015-2020. However, a special contribution of this paper will be observing of variations in the number of conceptions and births in parallel with variations in the average weekly air temperature by administrative districts in the Serbia-North region. The ratio between the number of conceptions during a calendar week with days of a certain average air temperature and live births that occur after 30-42 weeks later represents the degree of reproductive success indicating the level of fetal losses. Many recent studies indicate that there is a high correlation between the average weekly air temperature and clinically unregistered fetal losses that occur in the earliest stages of pregnancy. This effect is greatest in the first days after conception, potentially indicating the influence of an increase in air temperature on the occurrence of a conception error. The paper analyzes the relationship between changes in the number of days in five temperature ranges and changes in the number of pregnancies and live births as a positive pregnancy outcome. The results indicate that temperature extremes reduce the likelihood of a positive reproductive outcome. The expected increase in air temperatures and the occurrence of temperature extremes, under the influence of climate change, could further reduce the level of fertility in the Serbia-North region due to the specific seasonality of births and the large number of conceptions that occur during periods of particular temperature risk.